ANALISIS KEMISKINAN DI KAWASAN TIMUR INDONESIA - Saddam Tubaka (Jurnal Cita Ekonomika, 2019)
This study was conducted to analyze the effect of economic growth, income distribution, unemployment, education and health on poverty in Eastern Indonesia in 2013-2017. Independent variables used in this study are economic growth, income distribution, unemployment, education and health and poverty as dependent variable. The data used in this study are secondary data sourced from the Central Statistics Agency of Maluku Province consisting of time series data for 2013 - 2017 and cross section data for 12 provinces in Eastern Indonesia. The analytical method used is panel data regression analysis. The results showed that economic growth had a positive and not significant effect on poverty in Eastern Indonesia. Variable income distribution has a positive and not significant effect on poverty in Eastern Indonesia. The unemployment variable has a positive and significant effect on the poverty variable in Eastern Indonesia. Education and health variables have a positive and significant effect on poverty in Eastern Indonesia. The coefficient of determination is 0.993136, meaning that the poverty variable can be explained by variables of economic growth, income distribution, unemployment, education and health by 99.31%. Simultaneous test results (F test), showed variables of economic growth, income distribution, unemployment, education and health simultaneously had a significant effect on poverty in Eastern Indonesia.